Sensitivity enhancement of a wavelength interrogation-based optical fiber surface plasmon resonance sensor for hemoglobin concentration using barium titanate - Shi, Zhen-Jiang; Guo, Shi-Liang; Li, Xin; Li, Zhi-Quan; Meng, Shu-Han; Li, Chong-Zhen (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
In this paper, the performances of a wavelength interrogation-based optical fiber surface plasmon resonance sensor for hemoglobin (Hb) concentration is investigated by theoretical simulation. The proposed configuration incorporates optical fiber, 70 nm silver, 18 nm barium titanate (BaTiO3), and 2 nm zinc oxide. Simulation results show the sensor exhibits refractive index sensitivity of 4023 nm/RIU and concentration sensitivity of 10.0873 nm/(g·dL), along with Hb concentration varying from 0 to 14 g/dL. This paper especially focuses on the influence of BaTiO3 on the performances of the proposed sensor with light wavelength ranging from 350 to 1000 nm. Comparison analysis indicates sandwiching 18 nm BaTiO3 between sensing layers not only enhances the concentration sensitivity by 30.14% but also decreases the nonlinear error of the sensor from 0.68% to 0.63%. For a wavelength accuracy of 0.1 nm, the proposed sensor can provide a resolution of 0.0099 g/dL for Hb concentration detection.
Optica Applicata, Vol. 53, 2023, nr 2, s. 167-184
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; surface plasmon resonance; wavelength interrogation; barium titanate; sensitivity enhancement; hemoglobin concentration